Germanic Loanwords in Proto-Slavic - Kallio, Petri (Finnisch-Ugrische Forschungen, 2014)
Saskia Pronk-Tiethoff: The Germanic Loanwords in Proto-Slavic. (Leiden Studies in Indo-European 20.) Amsterdam –New York: Editions Rodopi B. V. 2013. X, 316 pp